Nosocomial transmission of influenza: A retrospective cross‐sectional study using next generation sequencing at a hospital in England (2012‐2014). Issue 6 (19th September 2019) - Blackburn, Ruth M.; Frampton, Dan; Smith, Catherine M.; Fragaszy, Ellen B.; Watson, Simon J.; Ferns, R. Bridget; Binter, Špela; Coen, Pietro G.; Grant, Paul; Shallcross, Laura J.; Kozlakidis, Zisis; Pillay, Deenan; et al.
Abstract: Background: The extent of transmission of influenza in hospital settings is poorly understood. Next generation sequencing may improve this by providing information on the genetic relatedness of viral strains. Objectives: We aimed to apply next generation sequencing to describe transmission in hospital and compare with methods based on routinely‐collected data. Methods: All influenza samples taken through routine care from patients at University College London Hospitals NHS Foundation Trust (September 2012 to March 2014) were included. We conducted Illumina sequencing and identified genetic clusters. We compared nosocomial transmission estimates defined using classical methods (based on time from admission to sample) and genetic clustering. We identified pairs of cases with space‐time links and assessed genetic relatedness. Results: We sequenced influenza sampled from 214 patients. There were 180 unique genetic strains, 16 (8.8%) of which seeded a new transmission chain. Nosocomial transmission was indicated for 32 (15.0%) cases using the classical definition and 34 (15.8%) based on genetic clustering. Of the 50 patients in a genetic cluster, 11 (22.0%) had known space‐time links with other cases in the same cluster. Genetic distances between pairs of cases with space‐time links were lower than for pairs without spatial links ( P < .001). Conclusions: Genetic data confirmed that nosocomial transmission contributes significantly to the hospital burden of influenza and elucidated transmission chains. Prospective next generation sequencing could support outbreak investigations and monitor the impact of infection and control measures.